2019
DOI: 10.1002/bip.23275
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanisms of GN‐2 derived peptides and peptoids against Escherichia coli

Abstract: Escherichia coli is the main etiological agent of urinary trait infections, able to form biofilms in indwelling devices, resulting in chronic infections which are refractory to antibiotics treatment. In this study, we investigated the antimicrobial and anti‐biofilm properties exerted against E. coli ATCC 25922, by a set of peptoids and peptides modeled upon the peptide GN‐2, previously reported as a valid antimicrobial agent. The putative antimicrobials were designed to evaluate the effect of cationicity, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…170 Similarly, Jenssen and co-workers identified a synthetic peptide GN-2 through quantitative structure activity relationship (QSAR) in silico methods and prepared a range of sequence-defined synthetic peptides and their corresponding peptoids, which mimicked the GN-2 structure, as well as the GN-2 peptide itself. 171 Interestingly, they found that structures that showed high planktonic antimicrobial activity showed poorer antibiofilm activity and vice versa. Peptoid materials generally showed superior E. coli antibiofilm activity, compared to the corresponding peptides, despite showing lower activity against planktonic bacteria.…”
Section: New Directions In Antibiofilm Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…170 Similarly, Jenssen and co-workers identified a synthetic peptide GN-2 through quantitative structure activity relationship (QSAR) in silico methods and prepared a range of sequence-defined synthetic peptides and their corresponding peptoids, which mimicked the GN-2 structure, as well as the GN-2 peptide itself. 171 Interestingly, they found that structures that showed high planktonic antimicrobial activity showed poorer antibiofilm activity and vice versa. Peptoid materials generally showed superior E. coli antibiofilm activity, compared to the corresponding peptides, despite showing lower activity against planktonic bacteria.…”
Section: New Directions In Antibiofilm Materialsmentioning
confidence: 99%
“…The authors explained this through consideration of the differences in backbone rigidity, different spatial arrangements of the charged and hydrophobic residues, as well as differences in hydrogen bonding capability, which were competing factors in determining potency against planktonic bacteria and biofilms. 171 One other important class of peptidomimetics are b-peptides. 85 Whilst typical a-peptides have both the amino and carboxylic acid functionality bound to the same carbon (the a-carbon), b-peptides are bound through the b-carbon (Fig.…”
Section: New Directions In Antibiofilm Materialsmentioning
confidence: 99%
“…Jenssen and co-workers have compared the antimicrobial activity of peptoids and their peptide counterpart against the same bacteria. [97] Although the peptide showed higher antimicrobial activity, the peptoid showed superior antibiofilm properties. The lack of an H-bond donor and the structural flexibility of peptoids are associated with the ability to penetrate bacterial membranes.…”
Section: Peptoidsmentioning
confidence: 99%
“…The lack of an H-bond donor and the structural flexibility of peptoids are associated with the ability to penetrate bacterial membranes. [97] Hybrid molecules such as α-peptide/α-peptoid and α-peptide/β-peptoid were also useful in developing AMPs with various activities and selectivity. The effect of elongating the side chain on an α-peptide or αpeptoid moiety for antimicrobial activity was examined.…”
Section: Peptoidsmentioning
confidence: 99%
“…A microtiter broth dilution method [62,63] was used to determine the MICs of antimicrobial peptides. For these tests, the bacterial inoculum was prepared in LB liquid medium (OD600 ≈ 0.02-0.05) and added to a 96-well titration plate.…”
Section: Minimum Inhibitory Concentration (Mic) and Growth Time-killmentioning
confidence: 99%